STRUCTURAL FUNCTIONAL ANALYSIS OF TSHWANE UNIVERSITY OF TECHNOLOGY: POST MERGER IMPLICATIONS - Phago, Kedibone; Baloyi, Mzamane (South African Journal of Higher Education, 2016)
Since 1997 upon the promulgation of Higher Education Act 101 of 1997, the higher education landscape has changed for good. This is partly because 36 public higher education institutions had to be merged and reduced to 21 as a government agenda to enhance the quality of education at the highest level. This merger process was expected to consider several democratic principles in order to facilitate the stakeholder consultation. These democratic principles include transparency, ownership, consultation and legitimacy. However, this article is an attempt to understand the efficacy of a functional structure of Tshwane University of Technology during this merger process. In this regard, a qualitative approach was used to facilitate the undertaking of data collection. In the final analysis, it is observed from collected data that the Tshwane University of Technology’s merger was destined for an implosion.